TOPIC PRESCRIPTION STRUCTURE OF PRESCRIPTION (International conference on multidisciplinary science, 2023)
A prescription is an important medical document that has  the healthcare provider's instructions for a patient's treatment. It acts as a legal and clinical communication tool between healthcare professionals and patients, detailing the specific medications, dosages, administrative methods, and duration of treatment. This abstract explores the essential components and structure of a prescription, emphasizing its significance in ensuring patient safety, optimizing the therapeutic outcomes, and adhering to legal and ethical standards in healthcare. Understanding the key elements and principles of prescription writing is vital for healthcare professionals to promote the effective and responsible patient care and treatment.